(untitled) (Journal of EAHIL, 2024)
Maintaining research registers and similar content can be resource intensive. Automation tools can help in identifying, assessing and describing content. This article describes some challenges and opportunities using automation to support coverage, keywording and improve sustainability for two research registers of health promotion effectiveness.